O emocional nos desvios comportamentais - Almeida, Ana Teresa Nunes Pinheiro Dias de (2012)
Although the question of the behavioural deviance has been a more and more current phenomena at our schoots and in society in general, it has been due to various factors, except to the influence of emotions. Thus, the main goal of this study consists in verifying the influence of emotions in behaviour and learning. From a methological point of view, this is a study of qualitative nature, using the Case Study. We have setected four cases of thirteen to fourteen year-old students with behavioural deviance. The instruments used in the data recollection were the inquiries to students and teachers, the drawíng. the scales and the interviews complemented with information of other school documents. The data analysis allowed us to know the students' family retationships as well as their interpersonal relationships at school and their resilience level. Furthermore, we have known the teachers' representations about emotions and behavioural deviance and the strategies they suggest to remediate the lack of emotion and the behavioural deviance of some students.